The role of Aspergillus fumigatus polysaccharides in host–pathogen interactions. (December 2019) - Zacharias, Caitlin A; Sheppard, Donald C
Abstract : Aspergillus fumigatus is a saprophytic mold that can cause infection in patients with impaired immunity or chronic lung diseases. The polysaccharide-rich cell wall of this fungus is a key point of contact with the host immune system. The availability of purified cell wall polysaccharides and mutant strains deficient in the production of these glycans has revealed that these glycans play an important role in the pathogenesis of A. fumigatus infections. Herein, we review our current understanding of the key polysaccharides present within the A. fumigatus cell wall, and their interactions with host cells and secreted factors during infection.